Modernization of the mechanism of the financial services market cybersecurity legal support - O. V. Brusakova; O. P. Getmanets (Law and Safety)
Due to the rapid development of digital technologies, the role of the Internet segment of the financial services market is actively increasing. That is why the issue of cybersecurity in this market is now gaining national importance and is becoming critical to national security. The methodological basis of the study is systemic, and the study used a comprehensive approach, which is manifested in the use of different methods of scientific knowledge depending on specific aspects of the study. The methodological basis of the study is the dialectical method of phenomena and processes cognition. In particular, the comparative legal method, the system and structural method, the statistical method, the logical legal method, the formal legal method and the method of analogy were used.